A Dipeptidyl Peptidase-4 Inhibitor Suppresses Macrophage Foam Cell Formation in Diabetic db/db Mice and Type 2 Diabetes Patients. (9th December 2018) - Terasaki, Michishige; Hiromura, Munenori; Mori, Yusaku; Kohashi, Kyoko; Kushima, Hideki; Koshibu, Masakazu; Saito, Tomomi; Yashima, Hironori; Watanabe, Takuya; Hirano, Tsutomu
Abstract : Dipeptidyl peptidase-4 (DPP-4) inhibitors could have antiatherosclerotic action, in addition to antihyperglycemic roles. Because macrophage foam cells are key components of atherosclerosis, we investigated the effect of the DPP-4 inhibitor teneligliptin on foam cell formation and its related gene expression levels in macrophages extracted from diabetic db/db ( C57BLKS/J Iar -+Lepr db /+Lepr db ) mice and type 2 diabetes (T2D) patients ex vivo. We incubated mouse peritoneal macrophages and human monocyte-derived macrophages differentiated by 7-day culture with oxidized low-density lipoprotein in the presence/absence of teneligliptin (10 nmol/L) for 18 hours. We observed remarkable suppression of foam cell formation by teneligliptin treatment ex vivo in macrophages isolated from diabetic db/db mice (32%) and T2D patients (38%); this effect was accompanied by a reduction of CD36 ( db/db mice, 43%; T2D patients, 46%) and acyl-coenzyme A: cholesterol acyltransferase-1 (ACAT-1) gene expression levels ( db/db mice, 47%; T2D patients, 45%). Molecular mechanisms underlying this effect are associated with downregulation of CD36 and ACAT-1 by teneligliptin. The suppressive effect of a DPP-4 inhibitor on foam cell formation in T2D is conserved across species and is worth studying to elucidate its potential as an intervention for antiatherogenesis in T2D patients.